Evaluation of an in situ QAM‐based Power Line Communication system for lithium‐ion batteries - Mahyar J. Koshkouei; Erik Kampert; Andrew D. Moore; Matthew D. Higgins (IET Electrical Systems in Transportation)
Abstract Power Line Communication (PLC) is used to transmit high‐fidelity data on internal cell characteristics from within instrumented cells to an external Battery Management System (BMS). Using PLC is beneficial, as it avoids the need for a complex and heavyweight wiring harness within a battery. The use of advanced modulation, such as Quadrature Amplitude Modulation (QAM), is considered here. The existing experimental results of lithium‐ion cell impedance characteristics for frequencies of 100 kHz–200 MHz are exploited in order to create a realistic battery model. This model is used to determine the effectiveness and optimal properties of PLC with QAM, as a means of in situ battery communication for Battery Electric Vehicles (BEVs) in combination with a real‐world dynamic drive profile. Simulations reveal that the performance of the PLC system is heavily dependent on the selected carrier frequency due to the significant changes in reactance and internal resistance of the lithium‐ion cells tested. Furthermore, cells placed in parallel display a decreased performance compared with cells in series. The results highlight that the optimal carrier frequency for in situ QAM‐based PLC for a lithium‐ion battery system is 30 MHz, and that additional signal conditioning is required for 4‐QAM and higher modulation orders.